(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article provides more accurate and complete information about the life and work of the famous Azerbaijani poet Nizami Ganjavi. The purpose of this is to attract a wide range of readers to the creative work of the poet and to further reveal its importance in the development of our literature.